ENVIRONMENTAL AGENDA OF PUBLIC ADMINISTRATION (A3P): ANALYSIS OF THE FEASIBILITY OF ACCESSION OF THE FEDERAL UNIVERSITY OF PARÁ (REMUNOM, 2024)
The theme of the Environment has been increasingly gaining ground in society,so that public and private institutions have implemented sustainable actions toachieve strategic objectives. This article aimed to analyze the feasibility ofadhesion of the Federal University of Pará (UFPA) to the Public AdministrationEnvironmental Agenda (A3P) through a structured questionnaire applied inthree sectors of the institution, chosen due to its relevance to the topic,addressing the five thematic axes proposed by A3P and carrying out adiagnosis of the feasibility of joining A3P, verifying how environmental issuesare included in UFPA. It was identified that UFPA has been advancing in theimplementation of several actions to adhere to the A3P, but several projects stillneed to be developed to consolidate this adherence and guarantee compliancewith current standards regarding sustainability.